New Rome-IV criteria of the functional dyspepsia (review) - A. A. Sheptulin; A. A. Kurbatova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To analyze the changes in the IV revision of Rome criteria of the functional dyspepsia (FD) in comparison to existing criteria. Key points. The definition of FD and its main variants - postprandial distress syndrome (PDS) and epigastric pain syndrome (EPS) in new criteria did not undergo major changes in comparison to previous edition. Frequent combination of PDS and EPS both with each other, with such symptoms as nausea and belching and some other diseases as gastroesophageal reflux disease and irritable bowel syndrome was demonstrated. It is, still, recommended to make the diagnosis of FD, being guided both by compliance of patients symptoms to Rome criteria and the absence of alarm symptoms. The major place in the treatment of PDS is occupied by prokinetics, in EPS treatment - by antisecretory medications. Conclusion. The fourth revision of Rome criteria of FD have certain advantages in comparison to the previous criteria, but at the same time preserve essential shortcomings.